2011
DOI: 10.1007/s13311-010-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

MRI in Rodent Models of Brain Disorders

Abstract: Summary: Magnetic resonance imaging (MRI) is a wellestablished tool in clinical practice and research on human neurological disorders. Translational MRI research utilizing rodent models of central nervous system (CNS) diseases is becoming popular with the increased availability of dedicated small animal MRI systems. Projects utilizing this technology typically fall into one of two categories: 1) true "pre-clinical" studies involving the use of MRI as a noninvasive disease monitoring tool which serves as a biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 146 publications
(150 reference statements)
0
85
0
Order By: Relevance
“…These models help advance the understanding and treatment options of CNS diseases in humans (15). MRI enables longitudinal, noninvasive neurological studies in experimental animal models without sacrificing the animals and provides important anatomical and physiologic information (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models help advance the understanding and treatment options of CNS diseases in humans (15). MRI enables longitudinal, noninvasive neurological studies in experimental animal models without sacrificing the animals and provides important anatomical and physiologic information (16).…”
Section: Discussionmentioning
confidence: 99%
“…MRI enables longitudinal, noninvasive neurological studies in experimental animal models without sacrificing the animals and provides important anatomical and physiologic information (16). After the first MRI study of a rat reported 30 years ago, the number of studies has increased, particularly in relation to the CNS (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Cell tracking technologies for acute ischemic brain injury FNE Gavins and HK Smith systems operate using greater field strengths − 4.7 to 11.7 T. 33 4.7 T machines and above enable the acquisition of higher resolution images with lower cell detection limits, and are required to generate sufficient resolution to image detail of añ 25 g (versus~80 kg) animal. Recently, MRI has become highly useful in real-time, noninvasive imaging of stem cell activity.…”
Section: Magnetic Resonance Imaging: Imaging With Magnetismmentioning
confidence: 99%
“…There is no single animal model that can faithfully reproduce all the pathological aspects of MS in humans. The available models complement each other to enable investigation of various features commonly observed in the human condition [43].…”
Section: Animal Models Of Multiple Sclerosis (Ms)mentioning
confidence: 99%